2012
DOI: 10.1080/01140671.2012.681386
|View full text |Cite
|
Sign up to set email alerts
|

Sink priority on ‘Hayward’ kiwifruit vines

Abstract: An experimental system based on girdled shoots was used to assess how vegetative competition alters the growth of 'Hayward' kiwifruit. Each shoot was pruned to length so that it contained four source leaves and a sink consisting of either a single fruit, a vegetative regrowth, or one fruit and a vegetative regrowth. Vegetative competition had the greatest effect on fruit growth when it occurred about five weeks after flowering, when fruit growth is maximal. When a single fruit was in competition with a defolia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The girdling of shoots or the trunk to prevent the basipetal movement of assimilates and plant growth regulators is an old technique that has been applied with variable success in many fruit tree species [12,31]. In kiwifruit, girdling of canes or the trunk during the early fruit developmental stages aims mainly at improving fruit size, while girdling applied during the later stages of fruit development (stages of slower fruit development) focuses mainly on increasing fruit dry matter [32][33][34][35]. In the present experiment, the girdling was applied at the end of summer and early autumn, when fruit growth is slower, aiming at improving fruit quality characteristics and storability.…”
Section: Discussionmentioning
confidence: 99%
“…The girdling of shoots or the trunk to prevent the basipetal movement of assimilates and plant growth regulators is an old technique that has been applied with variable success in many fruit tree species [12,31]. In kiwifruit, girdling of canes or the trunk during the early fruit developmental stages aims mainly at improving fruit size, while girdling applied during the later stages of fruit development (stages of slower fruit development) focuses mainly on increasing fruit dry matter [32][33][34][35]. In the present experiment, the girdling was applied at the end of summer and early autumn, when fruit growth is slower, aiming at improving fruit quality characteristics and storability.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been postulated that shoots have a stronger sink strength (ability to attract carbohydrate when supply is not limited) and sink priority (ability to compete when carbohydrate supply is limited) over fruits during the first 120 DAMB (Lacointe and Minchin, 2008). Afterwards, in case of competition for limited resources, vegetative growth continues at the expenses of fruit growth (Snelgar et al, 2012). Moreover, high temperatures strongly influence the photosynthates allocation between fruits and shoots, with increased vegetative vigor stimulated by high temperatures at the expenses of sugars accumulation in fruits, whose dry matter at harvest is lowered (Hall and Snelgar, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of kiwifruit have shown that factors that affect carbohydrate source supply to fruit sinks can influence their final growth and composition. These factors can include crop load [ 3 ], leaf-to-fruit (L:F) ratio [ 31 , 32 ], girdling [ 33 ], application of growth regulators [ 8 , 34 ], pollination [ 35 ], application of nitrogen fertiliser [ 36 ], light [ 37 ] and temperature [ 38 ]. Girdling (to prevent carbohydrate moving to nonfruit sinks e.g., roots) and thinning studies (to increase the leaf:fruit ratio) of ‘Hayward’ vines have shown that effects of changing carbohydrate source supply on fruit size generally occur during rapid fruit growth while effects on fruit dry matter accumulation are seen during the second stage of fruit growth [ 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%